Chemical Constituents from the Roots and Stems of Erycibe obtusifolia and Their In Vitro Antiviral Activity - Fan, Long; Wang, Ying; Liang, Ning; Huang, Xiao-Jun; Li, Man-Mei; Fan, Chun-Lin; Wu, Zhen-Long; Li, Yao-Lan; Ye, Wen-Cai (Planta Medica, 2013)
Three new quinic acid derivatives, 4-O-caffeoyl-3-O-sinapoylquinic acid methyl ester (1), 5-O-caffeoyl-4-O-syringoylquinic acid methyl ester (2), and 4-O-caffeoyl-3-O-syringoylquinic acid methyl ester (3), as well as four new coumarin glycosides, 7-O-(3-O-sinapoyl-β-D-glucopyranosyl)-6-methoxycoumarin (12), 7-O-(6-O-sinapoyl-β-D-glucopyranosyl)-6-methoxycoumarin (13), 7-O-(2-O-sinapoyl-β-D-glucopyranosyl)-6-methoxycoumarin (14), and 7-O-(6-O-syringoyl-β-D-glucopyranosyl)-6-methoxycoumarin (15), together with eight known compounds (4–11) were isolated from the roots and stems of Erycibe obtusifolia. Their structures were elucidated on the basis of spectroscopic analysis and chemical evidence. All the compounds were screened for their in vitro antiviral activity against respiratory syncytial virus with a cytopathic effect reduction assay. Among them, the di-O-caffeoyl quinates 8–11 displayed a potent in vitro anti-respiratory syncytial virus effect.
Keywords: Erycibe obtusifolia; Convolvulaceae; quinic acid derivative; coumarin glycoside; antivirus activity; respiratory syncytial virus